Utilisation of Mobile Learning in Mathematics Education: A Bibliometric Analysis Using The Scopus Database - Kania, Nia; Arifin, Zaenal; Rismayani, Rismayani; Bonyah, Ebenezer (EDUPEDIA Publisher, 2025)
The field of education has been profoundly transformed by advancements in information technology, particularly in teaching mathematics. This study thoroughly examines the current research trends in mobile learning (ML) for mathematics education until 2023. This study employed a bibliometric methodology to investigate the distribution patterns of publications in ML to achieve this goal. Specifically, the analysis focused on the following categories: timeline databases, document types of the most prolific countries, commonly used keywords by authors, and the evolution of thematic maps. Two hundred articles retrieved from the Scopus database were analysed and visualised using the Bibliometrix analysis suite from Scintopy software. The findings indicate that ML has emerged as a prominent area of research in mathematics education, with substantial growth observed since 2013, and the year 2019 reached its pinnacle with a record-breaking number of documents, precisely 26. Indonesia had the highest publishing output, with 16 publications, followed by the United States, Malaysia, South Africa, and the Philippines. The current trending subjects revolve around 'mobile learning', 'students', 'mathematics education', and 'e-learning'. There is no text provided. Following these fundamental principles, we can integrate ML in mathematics more comprehensively and extensively, enhancing future educational experiences. This research has the potential to establish a structure for comprehending previous studies and a systematic approach for conducting future research based on empirical evidence.